Opioid use patterns and risk characteristics among injured patients. Issue 1 (2nd January 2020) - Cochran, Gerald; Pacella, Maria L.; Ringwald, Whitney; Repine, Melissa; Hruschak, Valerie; Beaugard, Corinne; Sewall, Craig; Rosen, Danny; Alarcon, Louis H.; Tarkin, Ivan S.; Moloney, Gele B.; Corcos, Alain
Abstract: Background: Injured patients are at risk for prolonged opioid use after discharge from care. Limited evidence exists regarding how continued opioid use may be related to opioid medication misuse and opioid use disorder (OUD) following injury. This pilot study characterized opioid consumption patterns, health characteristics, and substance use among patients with active prescriptions for opioid medications following injury care. Methods: This study was a cross-sectional screening survey combined with medical record review from February 2017 to March 2018 conducted among outpatient trauma and orthopedic surgery clinic patients. Eligible patients were 18–64 years of age, admitted/discharged for an injury or trauma-related orthopedic surgery, returning for clinic follow-up ≤6 months post hospital discharge after the index injury, prescribed opioid pain medication at discharge, and currently taking an opioid medication (from discharge or a separate prescription post discharge). Data collected included demographic, substance use, mental health, and physical health information. Descriptive and univariate statistics were calculated to characterize the population and opioid-related risks. Results: Seventy-one participants completed the survey (92% response). Most individuals (≥75%) who screened positive for misuse or OUD reported no nonmedical/illicit opioid use in the year before the index injury. A positive depression screen was associated with a 3.88 times increased likelihood for misuse or OUD (95% confidence interval [CI] = 1.1–13.5). Nonopioid illicit drug use (odds ratio [OR] = 1.89, 95% CI = 1.1–3.4) and opioid craving (OR = 1.29, 95% CI = 1.1–1.5) were also associated with increased likelihood for misuse or OUD. Number of emergency department visits in the 3 years previous to the index injury was associated with a 22% likelihood of being misuse or OUD positive (95% CI = 1.0–1.5). Conclusions: Patients with behavioral health concerns and greater emergency department utilization may have heightened risk for experiencing adverse opioid-related outcomes. Future research must further establish these findings and possibly develop protocols to identify patients at risk prior to pain management planning.